Glucocorticoid receptor action in prostate cancer: the role of transcription factor crosstalk - Hiltunen, Johannes; Helminen, Laura; Paakinaho, Ville (Frontiers in Endocrinology, 2024)
Prostate cancer is one of the most prevalent malignancies and is primarily driven by aberrant androgen receptor (AR) signaling. While AR-targeted therapies form the cornerstone of prostate cancer treatment, they often inadvertently activate compensatory pathways, leading to therapy resistance. This resistance is frequently mediated through changes in transcription factor (TF) crosstalk, reshaping gene regulatory programs and ultimately weakening treatment efficacy. Consequently, investigating TF interactions has become crucial for understanding the mechanisms driving therapy-resistant cancers. Recent evidence has highlighted the crosstalk between the glucocorticoid receptor (GR) and AR, demonstrating that GR can induce prostate cancer therapy resistance by replacing the inactivated AR, thereby becoming a driver of the disease. In addition to this oncogenic role, GR has also been shown to act as a tumor suppressor in prostate cancer. Owing to this dual role and the widespread use of glucocorticoids as adjuvant therapy, it is essential to understand GR's actions across different stages of prostate cancer development. In this review, we explore the current knowledge of GR in prostate cancer, with a specific focus on its crosstalk with other TFs. GR can directly and indirectly interact with a variety of TFs, and these interactions vary significantly depending on the type of prostate cancer cells. By highlighting these crosstalk interactions, we aim to provide insights that can guide the research and development of new GRtargeted therapies to mitigate its harmful effects in prostate cancer.